Statin use and time to progression in men on active surveillance for prostate cancer. Issue 4 (November 2018) - Jayalath, Viranda; Nayan, Madhur; Finelli, Antonio; Komisarenki, Maria; Timilshina, Narhari; Kulkarni, Girish; Fleshner, Neil; Bhindi, Bimal; Evans, Andrew; Zlotta, Alexandre; Hamilton, Robert
Abstract Purpose Recent evidence suggests that statins may improve prostate cancer outcomes; however, their role in active surveillance (AS) is poorly characterized. We aimed to evaluate the association between statin use at diagnosis and time to progression on AS. Materials and Methods Data were obtained from a prospectively maintained cohort of men undergoing AS between 1995 and 2016 at our institution. All men satisfied the low-risk criteria: Gleason score <7, <4 positive cores, <50% involvement of any core, and prostate-specific antigen level <10.0 ng/dL. Kaplan–Meier curves and multivariable Cox proportional hazards were used to assess statin exposure at diagnosis and at time to pathological progression (failing to meet the low-risk criteria at biopsy) and therapeutic progression (first of pathological progression or initiation of definitive therapy). Reclassification at confirmatory biopsy (first postdiagnostic biopsy) and progression beyond confirmatory biopsy were evaluated independently. Results Low-risk criteria were met by 797 men. Reclassification at the confirmatory biopsy occurred in 194 (24%) men, 51 (26%) of whom were statin users. Statin use was not associated with reclassification at confirmatory biopsy (odds ratio (OR): 1.24, 95% confidence interval (CI): 0.77–1.99). Among the remaining 603 men (median age: 63 years; follow-up: 60 months; 23% statin users), 149 (24%) had pathologic progression, while 200 (33%) had therapeutic progression. Statin exposure was not associated with pathological (multivariable hazard ratio (HR) 0.79, 95% CI: 0.51–1.23) or therapeutic (multivariable-HR 0.81, 95% CI: 0.55–1.19) progression beyond the confirmatory biopsy. Sensitivity analyses did not alter conclusions. Conclusions In our study, statin use at diagnosis was not significantly protective against pathological or therapeutic progression in men undergoing AS for localized, low-risk prostate cancer.